2012
DOI: 10.1002/etc.2007
|View full text |Cite
|
Sign up to set email alerts
|

Integrated coastal effects study: Synthesis of findings

Abstract: Municipal wastewater discharges constitute a major source of contaminants of emerging concern (CECs) to coastal waters, yet uncertainty exists regarding their linkage to adverse biological effects such as endocrine disruption. Limited information is available concerning the types and fate of CECs discharged to the Southern California Bight (SCB) from municipal wastewater and their potential for ecological impacts. The present study investigated the impacts of CECs from ocean wastewater discharges on SCB fish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
1
19
2
Order By: Relevance
“…In the laboratory-acclimatized fish exposed to control seawater, plasma E2 levels were lower, often by an order of magnitude (<20 pg/ml) compared with E2 levels in feral fish (200À800 pg/mL; Supplemental Data, Figure S1). Another response previously observed in feral hornyhead turbot was decreased plasma T4 concentrations in fish collected near POTW effluent discharge zones compared with fish from a reference area [15]. The present study did not show this pattern of response after 2 wk of exposure in the laboratory.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In the laboratory-acclimatized fish exposed to control seawater, plasma E2 levels were lower, often by an order of magnitude (<20 pg/ml) compared with E2 levels in feral fish (200À800 pg/mL; Supplemental Data, Figure S1). Another response previously observed in feral hornyhead turbot was decreased plasma T4 concentrations in fish collected near POTW effluent discharge zones compared with fish from a reference area [15]. The present study did not show this pattern of response after 2 wk of exposure in the laboratory.…”
Section: Discussioncontrasting
confidence: 82%
“…Initial dilution ratios >100:1 are common. The use of lower effluent exposure concentrations was consistent with our objective to investigate biological responses to realistic environmental concentrations to help in interpreting data obtained in previous field studies [15].…”
Section: Discussionsupporting
confidence: 64%
“…However, examination of long-term monitoring data on fish community structure does not show signs of impact due to anthropogenic sources of contaminants [24]. Analysis of historical population data from 1970 to 2007 indicated that populations in the SCB are increasing at all outfall locations relative to the 1990s.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in coastal southern California, benthic Pleuronectiform fishes including the Dover sole ( Microstomus pacificus ) and hornyhead turbot ( Pleuronichthys verticalis )—species that live in direct physical contact with the ocean floor—have been documented with muscle burdens of total DDTs 3–4 times higher than those observed in white croaker ( Genyonemus lineatus ), a schooling species that swims above the substrate (Gossett et al, ; McDermott‐Ehrlich et al, ; see also Zeng and Tran, ). High burdens of 4‐NP have likewise been detected in hornyhead turbot from these same habitats (Maruya et al, ), and there is evidence that these fish may be experiencing adverse endocrine effects (Bay et al, ). Studies that examine not only the induction—but also the recovery or adaptation—of molecular and physiological responses to chemical exposure will therefore be essential to the use of gene expression patterns in benthic marine fishes as reliable biological indicators for environmental monitoring.…”
Section: Resultsmentioning
confidence: 96%